THE SYSTEM OF ARABIC TERMINOLOGY AND ITS INTERDISCIPLINARY DEVELOPMENT - Nurali Mavlanov (Western European Studies, 2025)
This article examines the system of Arabic terminology, tracing its historical development and interdisciplinary contributions across fields such as science, philosophy, medicine, and modern technology. It analyzes the structure of Arabic terms, rooted in the language’s morphological system of roots and patterns, and explores how historical translation movements and modern standardization efforts have shaped its terminology. The article highlights the role of Arabic in preserving and advancing knowledge during the Islamic Golden Age and its adaptation to contemporary interdisciplinary challenges. Challenges in standardizing terminology across Arabic dialects and integrating it into global scientific discourse are also discussed. The analysis underscores the dynamic nature of Arabic terminology and its significance in fostering interdisciplinary innovation
Keywords: Arabic terminology; morphology; root-and-pattern system